Jambu varieties performance under shading screens - Monteiro Ferreira, Silvia Marcela; Santana Muniz, Carla Caroline; Laurimar do Nascimento Andrade, Francisco; Fazzi Gomes, Rafaelle; da Silva Santos, Lucas (Revista Ceres, 2025)
Shading screens have been extensively used in leafy-vegetables production system. Nevertheless, there is still a substantial lack of knowledge regarding the effects of this technology on the performance of non-conventional vegetables such as jambu, a typical staple food with social and economic importance for the Amazon region. This study thus aimed to evaluate the effects of shading screens on the agronomic performance of two jambu varieties. The experiment was performed in a randomized block design, in a 4 x 2 factorial scheme (shading screens and varieties), with four replications. Plants were then evaluated for morphophysiological and yield parameters. As an outcome, there was no significant interaction between shading screens and varieties for assessed variables. On the other hand, the shading screen itself affected significantly jambu varieties yield. The 50%-shading screen for instance provided both higher fresh weight accumulation and higher shoot water content. Moreover, 50%-shading screen led to an increase in both productivity (Kg m-2) and yield (bunch m-2) by 46%, respectively. The use of 50%-shading screen improves the agronomic performance of jambu, hence being a suitable technological alternative available for the farmers.